2013
DOI: 10.1111/1462-2920.12103
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and evolutionary relationships of T7‐like podoviruses infecting marine cyanobacteria

Abstract: Phages are extremely abundant in the oceans, influencing the population dynamics, diversity and evolution of their hosts. Here we assessed the diversity and phylogenetic relationships among T7-like cyanophages using DNA polymerase (replication), major capsid (structural) and photosynthesis psbA (host-derived) genes from isolated phages. DNA polymerase and major capsid phylogeny divided them into two discrete clades with no evidence for gene exchange between clades. Clade A phages primarily infect Synechococcus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
82
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(93 citation statements)
references
References 79 publications
10
82
1
Order By: Relevance
“…% Cyanophage Sequences a broader range of hosts, whereas podo-and siphoviruses are specialists, infecting a narrow range of host species (20)(21)(22)(23)(24). To date no genetic marker has been clearly associated with phage morphological groups.…”
Section: Discussionmentioning
confidence: 99%
“…% Cyanophage Sequences a broader range of hosts, whereas podo-and siphoviruses are specialists, infecting a narrow range of host species (20)(21)(22)(23)(24). To date no genetic marker has been clearly associated with phage morphological groups.…”
Section: Discussionmentioning
confidence: 99%
“…Resistant Prochlorococcus substrains used in this study (Table S1) were initially selected for resistance to one of the following T7-like cyanopodoviruses: P-SSP7, P-TIP2, or P-GSP1 for MED4-derived strains, P-SSP2 for MIT9312-derived strains, and P-SSP1 or P-RSP1 for MIT9215-derived strains, as described by Avrani et al (14). These and the following additional T7-like cyanopodoviruses were used in the present study to assess resistance range and host population decline: P-TIP1 and P-TIP38 for MED4 strains, P-SSP3b for MIT9312-derived strains, and P-TIP39 for MIT9215-derived strains (14,74). The susceptible control cultures used in this study were isolated at the same time as the initial resistance substrains and were derived from the same ancestral colonies as their respective resistant substrains (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…All known marine cyanophages are tailed doublestranded DNA viruses belonging to three well-defined bacteriophage families, Myoviridae, Podoviridae, and Siphoviridae. Cyanomyoviruses tend to infect a broad range of hosts, often across Prochlorococcus and Synechococcus, while cyanopodoviruses and cyanosiphoviruses are generally host specific (5,(8)(9)(10)(11)(12)(13).…”
mentioning
confidence: 99%
“…Two discrete marine picocyanobacterial podovirus (MPP) phylogenetic clusters (MPP-A and MPP-B) were recognized based on the viral DNA polymerase gene (12). Recent studies suggested that MPP-B podoviruses are more abundant than MPP-A podoviruses (13,38,39). However, the relative abundances and spatial patterns of specific cyanopodovirus and cyanomyovirus phylogenetic lineages over the global ocean are still broadly unclear.…”
mentioning
confidence: 99%